Prognosis after surgical treatment for pancreatic cancer in patients aged 80 years or older: a multicenter study. (19th February 2016) - Sho, Masayuki; Murakami, Yoshiaki; Kawai, Manabu; Motoi, Fuyuhiko; Satoi, Sohei; Matsumoto, Ippei; Honda, Goro; Uemura, Kenichiro; Yanagimoto, Hiroaki; Kurata, Masanao; Akahori, Takahiro; Kinoshita, Shoichi; et al.
Abstract: Background: The optimal therapeutic strategy for very elderly pancreatic cancer patients remains to be determined. The aim of this study was to clarify the role of pancreatic resection in patients 80 years of age or older. Methods: A retrospective multicenter analysis of 1401 patients who had undergone pancreatic resection for pancreatic cancer was performed. The patients aged ≥80 years ( n  = 99) were compared with a control group <80 years of age ( n  = 1302). Results: There were no significant differences in the postoperative complications and mortality between the two groups. However, the prognosis of octogenarians was poorer than that of younger patients for both resectable and borderline resectable tumors. Importantly, there were few long‐term survivors in the elderly group, especially among those with borderline resectable pancreatic cancer. A multivariate analysis of the prognostic factors in the very elderly patients indicated that the completion of adjuvant chemotherapy was the only significant factor. In addition, preoperative albumin level was the only independent risk factor for a failure to complete adjuvant chemotherapy. Conclusion: This study demonstrates that the postoperative prognosis in octogenarian patients was not good as that in younger patients possibly due to less frequent completion of adjuvant chemotherapy. Abstract : Highlight Setting out to clarify the optimal therapeutic strategy for very elderly pancreatic cancer patients, Sho and colleagues demonstrated in this large multicenter study that the prognosis is poorer in octogenarians than in younger patients for both resectable and borderline resectable tumors, possibly due to less frequent completion of adjuvant chemotherapy.